Kritik terhadap Pemikiran Ahmad KhalÃ¢f AllÃ¢h tentang Kisah dalam al-QurâÃ¢n - Supriadi, Lalu (ISLAMICA: Jurnal Studi Keislaman, 2013)
There have been many methods and ways to understand the message of the stories narrated in the QurâÃ¢n, one of which being that which is introduced by the contemporary Muslim scholar named Ah}mad Khalaf AllÃ¢h. He is a specialist in the science of the story of the QurâÃ¢n, as it were. This paper deals with this man and his new approach in understanding such story. It highlights the background of the man and the intellectual environment that forced him to offer his new approach. Speaking of stories in the QurâÃ¢n as works of arts rather than as history, the man is considered unique in his own right. The paper slightly compares him to other scientists such as Muh}ammad âAbduh, Fakr al-DÃ®n al-RÃ¢zi and al-NaysÃ¢bÃ»rÃ® and found that his approach is capable of addressing many problematic issues in the QurâÃ¢n as far as stories are concerned, such as (1) the problem of inconsistence in the narration of the stories, (2) the notion of freedom of expression in the QurâÃ¢n, and (3) the fact that the QurâÃ¢n does entertain the idea of myth (asÃ¢tÃ®r). The paper dwells into these three issues.